Effect of alpha-lipoic acid on the removal of arsenic from arsenic-loaded isolated liver tissues of rat - Noor- (Bangladesh Pharmacological Society, 2006)
The patient of chronic arsenic toxicity shows oxidative stress. To overcome the oxidative stress, several antioxidants such as beta-carotene, ascorbic acid, α-tocopherol, zinc and selenium had been suggested in the treatment of chronic arsenic toxicity. In the present study universal antioxidant (both water and lipid soluble antioxidant) α-lipoic acid was used to examine the effectiveness of reducing the amount of arsenic from arsenic-loaded isolated liver tissues of rat. Isolated liver tissues of Long Evans Norwegian rats were cut into small pieces and incubated first in presence or absence of arsenic and then with different concentrations of α-lipoic acid during the second incubation. α-Lipoic acid decreases the amount of arsenic and malondialdehyde (MDA) in liver tissues as well as increases the reduced glutathione (GSH) level in dose dependent manner. These results suggest that α-lipoic acid remove arsenic from arsenic-loaded isolated liver tissues of rat.